Analisis Kinerja Keuangan Terhadap Retur Saham Pada Perusahaan Subsektor Kesehatan Yang Terdaftar Di Bursa Efek Indonesia - Rini Marlita; Puji Isyanto (CV. ITTC INDONESIA, 2024)
The impact of health subsector firms' financial performance on stock returns is investigated in this article, which focuses on companies listed on the Indonesia Stock Exchange. The purpose of this study is to analyse the relationship between health subsector IDX stock returns between 2021 and 2023 and several financial metrics like current ratio, return on assets, debt to equity, and earnings per share. Gathering and analysing numerical data to evaluate preexisting ideas or theories is what this study calls a quantitative verification approach. The study data was sourced from secondary sources, including the Indonesian Stock Exchange's official website (http://www.idx.co.id). Using purposive sampling approaches, a total of 27 data points were collected from 9 health subsector businesses during a 3-year period. To find out how one variable affects another, researchers employ multiple linear regression analysis. Companies operating in the health subsector often exhibit respectable financial performance, according to the study's findings, with sufficient profitability and liquidity ratios. A significantly high debt level is indicated by the solvency ratio, which needs care. The stock returns of these firms are unaffected by financial performance, according to further study.